DRUG CONSUMPTION ROOM IN UNITED KINGDOM - Lipipun, Jirawut (Rangsit Journal of Law and Society, 2022)
From the main principle that “Drug addicts are patients” will respond to this principle by having The “drug consumption room” under the management of the medical and public health works in cooperation with the local government and community. which works well in Federal Republic of Germany, Canada, Kingdom, Denmark, United Kingdom, etc. The main reason is Former drug users had to rely on drugs from illegal drug dealers. and must also hide from the prying eyes of the criminal justice system. had the opportunity to have a better alternative Get pure drugs under his health supervision by the state and not illegal. By providing the state drug consumption room, along with the actual medical treatment under the law, reducing the harm from drug use. for good and efficient management Drug users in this system must register drug users with the government. will be released from criminal liability Registration is therefore a way to reduce drug-related crimes. and make drug users confident in the public health system This allows the state to identify the person and the actual number. and also clearly distinguishes the behavior of being an addict Buy to buy or possess to consume. Clearly out of criminals in drug offenses. Not being stereotyped to prosecution, in which this group has been imprisoned in many prisons and reduced the use of temptation measures. Reduce the dangers of drug users themselves and reduce various dangers. to society from drug addicts